Antiretroviral Therapy (ART) Side Effect Impacted on Quality of Life, and Depressive Symptomatology: A Mixed-Method Study - Chen, Wei-Ti (2013)
Antiretroviral therapy (ART) is known for its side effects. In this paper, we describe ART side effects as experienced by Chinese HIV+ individuals. This study presents two stages of a research project, combining qualitative in-depth interviews (29 HIV+ participants) with quantitative statistical data analysis (N = 120). All data was collected between July 2005 to March 2008 at Beijing's Ditan Hospital. Consent was obtained from each participant for the qualitative interview and again for the quantitative survey. During in-depth interviews, Chinese HIV+ patients reported experiencing digestive discomfort, skin rashes, numbness, memory loss, nightmares, and dizziness, which not only brought them physical discomfort, but also interrupted different dimensions of their social lives. Furthermore, multiple regression analyses revealed that those who reported more severe side effects also experienced greater depressive mood after controlling for other clinical and psychosocial factors. ART side effects are one of the primary reasons causing HIV+ individuals to delay or stop taking life-saving medication; therefore, clinical interventions are critically needed to assist HIV+ individuals in managing ART side effects. ART side effects reinforced existing negative attitudes toward ART and lead to lower ART adherence. Future research should focus on developing culturally sensitive interventions to enhance HIV+ self-management, to alleviate physical and psychological burden from ART and HIV.